ANALISIS KAFEIN DALAM KOPI ROBUSTA (TORAJA) DAN KOPI ARABIKA (JAWA) DENGAN VARIASI SIKLUS PADA SOKLETASI - Tria Annisa Rizky; Chairul Saleh; Alimuddin - (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
The research about analysis of caffeine content on coffee Robusta (Toraja) and coffee Arabika (Jawa) with cycle variations using spectrophotometer UV has been done. Coffee extract obtained throughsoxhletation with ethanol 96 % and variation cycles used is 3, 6, 9, 12 and 15, tested with spectrophotometer UV at a wavelength of 272 nm. The result of this research was obtained the caffeine content in coffee Robusta (Toraja) for 3, 6, 9, 12, 15 cycles consecutive is 1.439 mg/L, 2.158 mg/L, 2.695 mg/L, 2.887 mg/L and 3.700 mg/L. The caffeine content obtained coffee Arabika (Jawa) for 3, 6, 9, 12, 15 cycles consecutive is 0.474 mg/L, 0.478 mg/L, 1.056 mg/L, 1.540 mg/L and 1.926 mg/L respectively.Keywords: Coffee Robusta, Coffee Arabika, Ethanol 96 %, Soxhletation, Caffeine, Spectrophotometer UV